2015
DOI: 10.1371/journal.pone.0117547
|View full text |Cite
|
Sign up to set email alerts
|

A High-Fat Diet Delays Age-Related Hearing Loss Progression in C57BL/6J Mice

Abstract: ObjectiveAge-related hearing loss (AHL), or presbycusis, is the most common sensory disorder among the elderly. We used C57BL/6J mice as an AHL model to determine a possible association between AHL and a high-fat diet (HFD).MethodsForty C57BL/6J mice were randomly assigned to a control or HFD group. Each group was divided into the following subgroups: 1-, 3-, 5- and 12-month groups (HFD, n = 5/subgroup; control, n = 5/subgroup). Nine CBA/N-slc mice were also used as a 12-month control (n = 5) or 12-month HFD (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
(52 reference statements)
2
20
0
Order By: Relevance
“…By determining the expression of Ucp2 under all environmental stimuli, it was confirmed that mitochondrial dysfunction was caused by oxidative stress [ 12 , 14 ]. Mitochondrial dysfunction has been observed to induce apoptosis in many studies [ 9 , 19 ], and we obtained similar results through histological analysis in this study. Thus, we discussed that the reduction of frequencies was influenced when the blood vessels were damaged, and substance exchange in the bloodstream was poor because of the hypoxic condition and HFD.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…By determining the expression of Ucp2 under all environmental stimuli, it was confirmed that mitochondrial dysfunction was caused by oxidative stress [ 12 , 14 ]. Mitochondrial dysfunction has been observed to induce apoptosis in many studies [ 9 , 19 ], and we obtained similar results through histological analysis in this study. Thus, we discussed that the reduction of frequencies was influenced when the blood vessels were damaged, and substance exchange in the bloodstream was poor because of the hypoxic condition and HFD.…”
Section: Discussionsupporting
confidence: 89%
“…However, when two or more stimuli were added, hearing loss was observed to occur over a short period of time. HFD significantly increases the content of fat in the body, affects sugar metabolism, restricts blood vessels, and causes metabolic diseases [ 19 ]. These effects could be demonstrated by the expression of Edn1 and ApoE in cells within the hearing organ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the animals used in this study were 5 weeks of age upon surgery and 8 to 9 weeks of age upon euthanasia, the presence of sensorineural hearing loss is unlikely. Indeed, ABR thresholds of the mice in the current study are similar to thresholds of normal hearing C57Bl6 mice (Fujita et al, 2015, Shi et al, 2015). Moreover, VGLUT changes occurred only in the CN ipsilateral to the kanamycin injection, whereas sensorineural hearing loss would presumably affect both sides equally.…”
Section: Discussionsupporting
confidence: 73%
“…However, post-hoc tests were not significant for any of the tested frequencies (one-way ANOVA: p = 0.278, p = 0.128, p = 0.236, p = 0.241 for 12, 16, 20, and 30 kHz, respectively, corrected for multiple comparisons). ABR thresholds of age-matched control animals were similar to ABR thresholds of normal-hearing C57Bl6 mice (Fujita et al, 2015, Shi et al, 2015). …”
Section: Resultsmentioning
confidence: 53%